Combination Early Initiation of Breastfeeding and Oxytocin Massage Increase Prolactin Levels - Titi Maharrani; Evi Yunita Nugrahini (Humanistic Network for Science and Technology (HNST), 2022)
Introduction: Breastmilk (ASI) is the best food for babies up to 2 years of age or older. By providing breast milk (ASI) reduces the risk of various infections and other diseases. The study aimed to identify the effect of the combination of IMD and Oxytocin Massage on Prolactin Hormone Levels in Post-partum Women. Methods: This research design was quasy experimental with post test only control group design. The sample of this research was taken by simple random sampling of 40 postpartum who were then divided into 4 groups (each group 10 postpartum) consisting of 1 control group and 3 treatment groups. The dependent variable was early breastfeeding initiation and oxytocin massage, while the dependent variable was the level of hormone prolactin. Our treatment was oxytocin massage which given for 3 days from the first until the third day of puerperium. Oxytocin massage given two times a day at 08.00 and 16.00 for 3 minutes every treatment. Measurement of prolactin hormonelevels through serum taken on day 3 post partum. Prolactin hormone levels were examined at the Kedungdoro Laboratory using the ELFA method. Results: Anova test results in the four groups resulted in a p-value of 0.000, which means that there was a significant difference in the mean prolactin levels between the control group and the treatment group. Conclusion: All normal postpartum mothers are given a combination of IMD and oxytocin massage so that it can increase prolactin hormoneand the success of exclusive breastfeeding. Keywords: early initiation of breastfeeding; oxytocin massage; prolactin hormone